2013
DOI: 10.1088/1367-2630/15/1/013061
|View full text |Cite
|
Sign up to set email alerts
|

Topology bifurcation of a magnetic flux surface in magnetized plasmas

Abstract: Bifurcation phenomena in the radial propagation of a heat pulse driven by modulated electron cyclotron heating are observed in the Large Helical Device. There are two patterns of heat pulse propagation observed in the flat temperature region. One is a bi-directional slow heat pulse propagation observed in the fast magnetic shear drop and the other is a fast heat pulse propagation observed in the slow magnetic shear drop. This bifurcation in the heat pulse propagation suggests the topology bifurcation of a magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 29 publications
6
35
0
Order By: Relevance
“…The 3D effects have been intensely investigated so far in various devices and these investigations have made significant progress in the understanding of transport features [7,8,28,30,31,32,33,34,35]. The modifications of transport are caused by the stochasticity of field lines or by the 3D deformation of magnetic flux tubes [36,37]. The outermost region is called the laminar zone [38] or edge surface layers [1], where parallel correlation along field lines still persists to some extent, i.e., K L (Kolmogorov length) > C L (connection length to divertor plates).…”
Section: Introductionmentioning
confidence: 99%
“…The 3D effects have been intensely investigated so far in various devices and these investigations have made significant progress in the understanding of transport features [7,8,28,30,31,32,33,34,35]. The modifications of transport are caused by the stochasticity of field lines or by the 3D deformation of magnetic flux tubes [36,37]. The outermost region is called the laminar zone [38] or edge surface layers [1], where parallel correlation along field lines still persists to some extent, i.e., K L (Kolmogorov length) > C L (connection length to divertor plates).…”
Section: Introductionmentioning
confidence: 99%
“…At the bottom of the temperature drop (3.7 s), i/2p=1/2 is realized with gentle gradient (weak magnetic shear) at the core region and the flattening of the electron temperature around the e-ITB is observed as shown in Fig.10 (c)-1. It was reported that the stochastization can occur in the core region when the weak magnetic shear is realized near i/2p=1/2 and causes the flattening of the density and temperature profiles [19][20][21][22]. It was also reported that the required ECRH power to form and sustain the e-ITB is higher when the stochastic region exists in the core region of the target plasma [15].…”
Section: Evaluation Of the E-itb Performance With A Partial-coverage mentioning
confidence: 99%
“…By comparing with detailed model calculations it was shown that the generation of the seed island could be attributed to toroidal coupling effects leading to the generation of 2/1 perturbation from a 1/1 central mode or that of 3/2 from a 2/2 harmonic of the central mode. A novel technique to experimentally distinguish the topological distinctions between a magnetic island, a partially stochastic island and a fully stochastic region was reported in [22]. The technique rested on the basic idea of propagating a heat pulse (using a modulated ECH source) and measuring the propagation speed of the pulse as it traversed the radial extent of the plasma.…”
Section: Waves and Instabilities 221 Theory Modelling Simulationsmentioning
confidence: 99%